2002
DOI: 10.2151/jmsj.80.897
|View full text |Cite
|
Sign up to set email alerts
|

Ozonesonde Observations in the Equatorial Eastern Pacific. The Shoyo-Maru Survey.

Abstract: We have conducted GPS radiosonde and ozonesonde observations on board the research vessel ''Shoyo-Maru'' in the equatorial eastern Pacific. These observations took place in September and October 1999 as a part of the Soundings of Ozone and Water in the Equatorial Region (SOWER)/Pacific mission. The mean profile of ozone is similar to that for the dry season (September to October) at San Cristóbal, Galá pagos (0.9 S, 89.6 W) located in the equatorial eastern Pacific. The mean tropospheric ozone concentration is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…The experiments also showed that a large part of the air in the wet layer comes from the marine boundary layer, lifted by convections. These results support the speculation by Shiotani et al (2002) that northerly winds bring in wet air from the ITCZ.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The experiments also showed that a large part of the air in the wet layer comes from the marine boundary layer, lifted by convections. These results support the speculation by Shiotani et al (2002) that northerly winds bring in wet air from the ITCZ.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the particles in the dry parts above and below the layered structure come from southeast almost horizontally. These results are consistent with the observational fact that wet parts of the layered structures corresponded to northerly winds, and give a support to the suggestion by Shiotani et al (2002) that wet air came from the ITCZ by horizontal advection.…”
Section: Particle Transport Experimentssupporting
confidence: 91%
See 2 more Smart Citations
“…most likely caused by biomass burning. Their results are in accordance with the observations made over the equatorial eastern pacific, Cristobal, Galapagos (0.9 • S; 89.6 • W) by Shiotani et al (2002). A review by Staehelin et al (2001) addressed that the satellite and ground-based measurements show no significant ozone trends in the tropics but significant long-term negative trends of 2-4 % in the northern and southern mid-latitudes.…”
Section: Introductionsupporting
confidence: 85%